Life among the Indian fighters - Reger, James P. (San Diego, CA : Lucent Books, 1998)
Details how white trappers, explorers, and pathfinders engaged in violent encounters with Indians during the late eighteenth and early nineteenth centuries, both east and west of the Mississippi River.
Includes bibliographical references (p. 113-122) and index.
Keywords: Pioneers -- West (U.S.) -- History -- Juvenile literature; Pioneers -- West (U.S.) -- Biography -- Juvenile literature; Frontier and pioneer life -- West (U.S.) -- Juvenile literature; Indians of North America -- Wars -- West (U.S.) -- Juvenile literature; Pioneers; Frontier and pioneer life; Indians of North America -- Wars; West (U.S.) -- Biography -- Juvenile literature